Influence of Rock Wettability on Reservoir-Scale CO2 Geo-Sequestration - Al-Khdheeawi, Emad Abdulhusain Fakher (Curtin University, 2020)
The focus of this research is to investigate the influence of rock wettability on CO2 movement through porous media. By performing different multiphase flow reservoir simulations on a hectometre scale, this research investigates the effects of wettability, wettability spatial distribution, and factors affecting wettability on the efficiency of CO2 trapping mechanisms. The results of this research show that reservoir wettability significantly influences CO2 storage efficiency and that water-wet reservoirs are preferable CO2 sinks.